2019
DOI: 10.18203/2320-1770.ijrcog20190971
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and practices of cervical cancer screening among women in Rajnandgaon district, central India: health education is the need of the hour

Abstract: Background: Cervical cancer is a leading cause of morbidity and mortality among rural women in India. Early screening has been shown to be the most effective measure to prevent the disease. However, lack of awareness, lack of infrastructure, social stigma and fear are barriers to cervical cancer screening. The study was undertaken to assess the knowledge and practice among rural women regarding cervical cancer and screening tests with the aim of helping health professionals to revise policies and practices. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
(19 reference statements)
0
0
0
Order By: Relevance
“…The majority reported lack of knowledge about screening as a cause of not getting screening test done (68.9%). In a study by Armo et al, (2019) conducted in a tertiary care institute of Chhattisgarh India, only 8.1% had heard of cervical cancer screening, which was lower than our study where 24.2% women were aware. This highlights the rising awareness about cervical cancer.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…The majority reported lack of knowledge about screening as a cause of not getting screening test done (68.9%). In a study by Armo et al, (2019) conducted in a tertiary care institute of Chhattisgarh India, only 8.1% had heard of cervical cancer screening, which was lower than our study where 24.2% women were aware. This highlights the rising awareness about cervical cancer.…”
Section: Discussioncontrasting
confidence: 94%
“…Self-sampling which is more woman friendly may prove to be an important tool to improve screening coverage. In the study Armo et al, (2019), only 2% had undergone previous screening, similar to our study where only 11.2% had past screening experience. Several studies had shown that given the opportunity, women would like to get themselves screened.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation